Smoking as a risk factor for dyslipidemia: study among type 2 diabetes mellitus patients on private hospital in Yogyakarta - Christine Patramurti; Dita Maria Virginia (Faculty of Pharmacy, Universitas Pancasila, 2025)
Smoking behavior is known to be a significant factor that has adverse effects on people with type 2 diabetes (T2DM). Nicotine in cigarettes stimulate adrenoreceptors and promotes lipolysis, leading to the synthesis of free fatty acids, which in turn increase the susceptibility to dyslipidemia and the development of cardiovascular disorders. This study aimed to examine the relationship between smoking status and the occurrence of dyslipidemia in patients with T2DM in a private hospital in Yogyakarta. A total of 107 T2DM patients participated in this cross-sectional observational study. Through live interviews, we collected smoking status conducted using the Fagerström Test for Nicotine Dependence (FTND) questionnaire. The fasting blood samples taken from participants were used to analyze the lipid profiles, including triglycerides (TG), total cholesterol, low-density lipoprotein (LDL), and high-density lipoprotein (HDL). The chi-square test revealed a significant association between smoking status and the risk of dyslipidemia among the participants, with χ²(2) = 13.463, p = 0.001. The findings suggest that smoking increases the risk of dyslipidemia among T2DM patients. These results highlight the importance of smoking cessation as a preventive measure to reduce metabolic complications in individuals with T2DM.